Grounding of premises and equipment (Power quality)
This video is an extension of the previous material on system grounding. It provides an overview of different grounding philosophies and methods, with the focus on customer premises and equipment. It identifies applicable industry codes and standards, as well as the reasoning behind many of the common acceptable grounding arrangements for premises and equipment. This program examines multiple power sources, building electrode systems, multiple buildings, equipment grounds, grounding of generators and UPSs, grounding of unit substations and switching centers, and grounding for static and lightning protection.